Effect of Biochar on the Cracking of Tar from the Pyrolysis of a Pine Sawdust in a Fixed Bed Reactor. (August 2015) - Zhang, Z.Z.; Zhu, M.M.; Liu, P.F.; Wan, W.C.; Zhou, W.X.; Chan, Y.L.; Zhang, D.K.
Abstract: The effect of biochar on the cracking of the tar from pyrolysis of a pine sawdust was experimentally studied. The pine sawdust was pyrolyzed in a fixed bed reactor at 1123K with and without a pine sawdust biochar placed downstream of the pyrolysis process to crack the pyrolysis tar. The cracking temperatures tested were 923, 1023 and 1123K and the vapour residence times of the tar passing through the biochar studied were 0, 1.2, 2.3 and 3.8s. The pyrolysis liquid yield decreased and pyrolysis gas yield increased with increasing biochar cracking temperature and the vapour residence time. The main pyrolysis gases were H2, CO, CH4 and CO2 . As the cracking temperature increased, the H2 yield increased while CH4 yield decreased. The CO concentration decreased when the cracking temperature increased from 973K to 1023K but then increased when the temperature continued to increase. The trend of the change of CO2 concentration as a function of the cracking temperature was opposite to that of CO. As the vapour residence time increased, the yields of H2 and CO2 increased while CH4 and CO yields decreased.